Excited Triplet State Interactions of Fluoroquinolone Norfloxacin with Natural Organic Matter: A Laser Spectroscopy Study - Niu, X.; Moore, E.; Croue, Jean-Philippe (American Chemical Society, 2018)
© 2018 American Chemical Society. In sunlit waters, the fate of fluoroquinolone antibiotics is significantly impacted by photodegradation. The mechanism of how natural organic matter (NOM) participates in the reaction has been frequently studied but still remains unclear. In this work, the interactions between the excited triplet state of the fluoroquinolone antibiotic norfloxacin (3NOR*) and a variety of NOM extracts were investigated using time-resolved laser spectroscopy. The observed transient absorption spectrum of 3NOR* showed a maximum at ca. 600 nm, and global fitting gave a lifetime of 1.0 µs for 3NOR* in phosphate buffer at pH = 7.5. Quenching of 3NOR* by Suwannee River hydrophobic acids (HPO), Beaufort River HPO, and Gartempe River HPO yielded rate constants of 1.8, 2.6, and 4.5 (×107 molC-1 s-1) respectively, whereas HPO from South Platte River unexpectedly increased the lifetime of 3NOR* with an as yet unknown mechanism. Concurrent photodegradation experiments of NOR (5 µM) in the presence of these NOM were also performed using a sunlight simulator. In general, the effects of NOM on the photodegradation rate of NOR were in agreement with observations from transient absorption studies. We suggest that adsorption of NOR to NOM is one of the major factors contributing to the observed quenching. These results yield a new insight into the likely role of NOM in sunlight-induced degradation of micropollutants.